2019
DOI: 10.1001/jamacardio.2018.4628
|View full text |Cite
|
Sign up to set email alerts
|

Association of All-Cause and Cardiovascular Mortality With High Levels of Physical Activity and Concurrent Coronary Artery Calcification

Abstract: IMPORTANCE Few data are available to guide clinical recommendations for individuals with high levels of physical activity in the presence of clinically significant coronary artery calcification (CAC). OBJECTIVE To assess the association among high levels of physical activity, prevalent CAC, and subsequent mortality risk. DESIGN, SETTING, AND PARTICIPANTS The Cooper Center Longitudinal Study is a prospective observational study of patients from the Cooper Clinic, a preventive medicine facility. The present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
139
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(148 citation statements)
references
References 33 publications
5
139
0
4
Order By: Relevance
“…Exercise-induced hypertension, systemic inflammation with repeated bouts of exercise and exercise-induced parathyroid hormone increases may also be involved in development of calcified CAD (39). Importantly, even with higher coronary artery calcium levels in highly active subjects than in the more sedentary population, active subjects did not have increased all-cause or CVD mortality as compared to sedentary subjects in a large 10-year follow-up study (42).…”
Section: Coronary Artery Diseasementioning
confidence: 97%
See 1 more Smart Citation
“…Exercise-induced hypertension, systemic inflammation with repeated bouts of exercise and exercise-induced parathyroid hormone increases may also be involved in development of calcified CAD (39). Importantly, even with higher coronary artery calcium levels in highly active subjects than in the more sedentary population, active subjects did not have increased all-cause or CVD mortality as compared to sedentary subjects in a large 10-year follow-up study (42).…”
Section: Coronary Artery Diseasementioning
confidence: 97%
“…Although moderate exercise reduces the risk of a cardiovascular event from coronary artery disease, recent cross-sectional studies have suggested a dose-dependent relation between life-long exposure to physical activity and the burden of myocardial fibrosis (39)(40)(41), coronary artery calcification (39,42,43) and atrial fibrillation in highly active subjects (44)(45)(46)(47). It is important to note that most of these studies are cross-sectional observational studies, and that a causal link between exercise and these pathophysiological processes has not been established.…”
Section: Long-term Cardiovascular Risks Associated With Strenuous Phymentioning
confidence: 99%
“…[3][4][5] These studies have suggested a dose-dependent relation between lifelong exposure to physical activity and calcified coronary artery disease (CAD). [3][4][5][6] This relationship, however, may seem contra intuitive, based upon the health and longevity of athletic subjects.…”
Section: Introductionmentioning
confidence: 99%
“…9 With such mounting evidence, not surprisingly, the American College of Cardiology has recently recommended that physicians use CAC to help reclassify patients with borderline to intermediate risk (10-year risk between 5% and 20%) to guide the initiation of have shown that some patients who are more physically fit, including marathon runners 11 and athletes 12,13 have higher levels of CAC than age-matched controls, but do not have increased cardiovascular morbidity and mortality. 14 This clinical paradox suggest that measuring plaque burden alone is not enough to risk stratify all patients.…”
Section: Coronary Artery Calcification As a Measure Of Cardiovascularmentioning
confidence: 99%